PJMHS 2022
DOI: 10.53350/pjmhs22165492
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study to Analyze the HBA1C and LIPID Profile in Type 2 Diabetic Patients with and without Diabetic Complications

Abstract: Aim: To compare the levels of HbA1c and lipid profile in type 2 diabetic patients with and without diabetic complications. Study design: A case-control study Place and Duration: This study was conducted at Bilawal Medical College for Boys at LUMHS Jamshoro Pakistan from September 2020 and September 2021 Methodology: The study sample size was n=140 type 2 diabetic patients. Thirty patients with DM 2 were used as controls, while 110 diabetic patients with problems such as neuropathy, retinopathy, and hypertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Hazari et al found that individuals with type II DM and DPN have prominent changes in their foot kinematics and kinetics, putting them at a higher risk for foot ulceration with underlying neuropathy and biomechanical manifestations 15 . A higher degree of functional impairment, a reduction in health-related quality of life, and difficulties with everyday tasks are all linked to painful DPN 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Hazari et al found that individuals with type II DM and DPN have prominent changes in their foot kinematics and kinetics, putting them at a higher risk for foot ulceration with underlying neuropathy and biomechanical manifestations 15 . A higher degree of functional impairment, a reduction in health-related quality of life, and difficulties with everyday tasks are all linked to painful DPN 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%